ROMAN STATE & CHRISTIAN CHURCH. A COLLECTION OF LEGAL DOCUMENTS TO A.D. 535. - Coleman-Norton, Paul R. (Paul Robinson) (WIPF AND STOCK, 2018)
This collection of legal documents affecting the Christian Church in the Roman Empire is the first its kind in any language. In time the monuments here translated cover the period from the foundation of the Church to the deposition of Romulus Augustulus, the last emperor in the West (476), and to the publication of the second (and only extant) edition of the Code of Justinian I, the most conspicuous champion of Caesaropapism in the East (534)--each terminus ad quem being an arbitrary, but a natural, limit. The character of the originals, which are mostly in either Greek or Latin, is strictly secular, that is, the documents emanate from the State's officials, ordinarily the emperors, and thus expose the State's attitude toward the Church. --From the Introduction.
Keywords: Church and state -- Rome.; Ecclesiastical law -- Rome.; Church history -- Primitive and early church, ca. 30-600.; Église et État -- Rome.; Droit ecclésiastique -- Rome.; Église -- Histoire -- ca 30-600 (Église primitive); Canon & Ecclesiastical Law.; Christian Church.; RELIGION.; Christian Education.; Church and state; Church history -- Primitive and early church; Ecclesiastical law; Rome (Empire); 30-600